C-Reactive Protein/Albumin Ratio as Predictor of COVID-19 Severity and Mortality - Ali Hashim Ibrahim, Jehan; Emad Abbas, Zahraa (South Asian Journal of Social Sciences and Humanities, 2025)
Background: Early detection of COVID-19 patients with a higher risk of infection advancement can help tailor treatment plans more specifically and ensure better allocation of healthcare resources. Both C-reactive protein also albumin serve as markers that are sensitive to inflammation. Study objective: evaluate the ability of CRP/ and Alb proportion in the prediction of cruelty and mortality of COVID-19 infection. Method: sample of 130 clients with COVID that confirmed outcomes entered the private nursing home medical city, Baghdad, Iraq, between January - October 2023. Patients are divided into mild, moderate and severe, and into dead and alive patients. To predict disease progression, CRP, albumin and CRPratio were evaluated on admission. Results: A study of 130 patients with COVID-19 infection, mean age of (53.80 ± 16.33) years old, (48.5%) of patients are females, while (51.5%) of patients are males. (66.92%) of patients have severe infection, while (33.08%) of them have non-severe (mild and moderate) infection with COVID-19. High CRPratio occurs more in severe COVID infection and those who died than in non-severe (mild and moderate) and those who were discharged alive, respectively. Conclusion: CRP/and albumin percentage may serve consider early indicator of the development of severe illness or death, offering a predictive biomarker to assess risk and guiding the clinical interventions of COVID-19 clients.